(3EOGQI GdehGQO GdHTQjI (B:s (3EJLGgGJ h eeGQSGJ (B/s - (3HQHQ, cGeds ((3HjQhJ(B: s (3OGQ Gdefgd GddHfGfj(B, s, 2008)
(3JfGhd GdcJGH hXGFa EOGQI GdehGQO GdHTQjI GdCSGSjI hbGe HJafjOgG hTQMgG hJaUjdgG HfGA Ydi GdCUhd GdfXQjI hGdNHQI GdYedjI GdWhjdI(B. (3CSgH aj GdMOjK Yf GdGSJbWGH hGdJYjjf HeG ajgG ef JMdjd GdhXGFa hGdhUa hGdJhUja GdhXjaj hGdGNJjGQ hGdJYjjf(B. (3hef Ke aj JMajR GdYGedjf hJOQjHge hJfejI bOQGJge(B. (3hJfGhd aj GdaUd GdCNjQ eG jZfj GdcJGH hGdHMK Mhd GdbVGjG GdeYGUQI aj GOGQI GdehGQO GdHTQjI(B.s
(3HjHdjhZQGajG(B: (3U(B. 317s
Keywords: (3EOGQI GdCaQGOs; (3GdehXahfs; (3ehGQO HTQjIs